The Impact of Transformational Leadership and Perceived Leadership Effectiveness on Organizational Commitment of Public Sector Workers in Kwara State, Nigeria - Ajia, Abdulmumin Yinka (Management Analysis Journal, 2021)
The importance of leadership in organizational outcome cannot be overstated. This study showed that perceived leadership effectiveness predicts positive organizational outcome in Nigeria better than transformational leadership when paired together. However, because of its inherent positive attributes, transformational leadership when augmented by leadership effectiveness and practices can make public institutions more effective and efficient in its service delivery and in its response to the citizenry. Findings from this survey research support the general theory that leadership is a major determinant of organizational outcome and supports the universal applicability of transformational leadership theories.